Development of Interactive Learning Multimedia Indonesia’s Cultural Diversity Material in Social Sciences Learning for Grade IV Elementary School Students - Sari, Ni Kadek Dwi Puspita; Wiyasa, I Komang Ngurah (Universitas Pendidikan Ganesha, 2021)
Implementation of distance learning in elementary school during the Covid-19 pandemic, through pre-research observations it was found that many use monotonous learning media causing students get bored in practice distance learning. Elementary school students make social sciences as their least preferred content and the low knowledge of elementary school students about the diversity of national cultures becomes a serious problem and must be addressed immediately. This research aims to developed learning media in the form of interactive learning multimedia material on Indonesia cultural diversity in social sciences learning for fourth grade elementary school students. This research is a type of R&D (Research and Development) using the ADDIE development model. This research was involved 3 validators namely material, instructional design, and media experts as well as reviewers 1 teacher and 12 grade fourth elementary school students. Data collection methods and data analysis using questionnaire and descriptive analysis methods. In trials by material experts, the score percentage of 90%, by learning design experts with a score percentage of 92,5%, media experts obtained results with a score percentage of 95%, so from the experts obtained category A very good qualification (very feasible). The results of the review from 1 grade IV elementary school teacher with a score percentage of 91.7%, review of 3 students in individual trials with a score percentage of 91.1%, the results of user reviews 12 students in the small group trial with a score percentage of 93.9%, were in the category A very good qualification (very feasible). Based on the result that obtained, the interactive learning multimedia content material Indonesia’s cultural diversity is very feasible and can be used in social sciences learning for fourth grade students of Elementary School.